Sistem Pendidikan SD al-Anwar Kota Pasuruan: Sebuah Sistem Gabungan Antara Sentralisasi dan Desentralisasi - Nursaman (Tarbawi : Jurnal Studi Pendidikan Islami, 2023)
The issue of decentralization refers to the extent to which authority has been delegated, authority from one level of management to the next level of management that is below it, while centralization is the opposite or remains held at the top level. The issue here is not whether an organization must decentralize, but to what extent it is decentralized. For example, basic education management tends towards centralization or decentralization. Or even a combination of centralization and decentralization. Let's take the example of the case of basic education management in an Islamic boarding school environment. Private basic education institutions that implement a combination of centralized and decentralized systems, one of which is AlAnwar Elementary School, Pasuruan City, which in certain parts such as additional curriculum and operational implementation implements both decentralization and centralization